(untitled) (LACCEI, 2024)
Monetary policy is a key tool to stabilize an economy as well as to boost it. In the present study we seek to demonstrate that there was a causal relationship in the Granger sense between monetary policy and economic cycles in Peru during 2000 - 2019 since the evolution of the monetary policy interest rate was empirically analyzed, in its role as an operational instrument of monetary policy in the economic cycles in Peru during 2000 - 2019 and the effects of monetary policy on the behavior of the real exchange rate and the terms of trade and its impact on economic cycles in Peru during the aforementioned period. One of the relevant findings is that the real interest rate had a significant influence on GDP and negatively with respect to the first and second lags. On the other hand, the terms of trade had a significant influence on GDP, being positive and negative with respect to the first and second lags, and the increases in the expected price of metal and food exports caused an increase in investment demand in the export sector of the country. country. This economic progress occurred at such a rapid pace that it offset and exceeded the losses caused by the excessive consumption of capital goods and the clumsy reversals of expansionary monetary policy.